2012
DOI: 10.1371/journal.pone.0031329
|View full text |Cite
|
Sign up to set email alerts
|

Massive Consumption of Gelatinous Plankton by Mediterranean Apex Predators

Abstract: Stable isotopes of carbon and nitrogen were used to test the hypothesis that stomach content analysis has systematically overlooked the consumption of gelatinous zooplankton by pelagic mesopredators and apex predators. The results strongly supported a major role of gelatinous plankton in the diet of bluefin tuna (Thunnus thynnus), little tunny (Euthynnus alletteratus), spearfish (Tetrapturus belone) and swordfish (Xiphias gladius). Loggerhead sea turtles (Caretta caretta) in the oceanic stage and ocean sunfish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(148 citation statements)
references
References 59 publications
8
125
0
2
Order By: Relevance
“…The dispersal pattern of young loggerhead sea turtles from Cape Verde has recently been estimated from particle tracking models and drifter trajectories (Monzon- 72 0 0 74 3 0 76 2 0 78 13 0 80 6 0 82 12 0 84 11 0 86 7 1 88 3 1 90 0 1 92 0 3 94 0 1 96 0 0 98 0 2 100 1 1 102 0 0 Table 1 (Bjorndal 1997, Revelles et al 2007, Frick et al 2009, Cardona et al 2012) and a recent study on leatherback sea turtles Dermochelys coriacea revealed low macrozooplankton biomass and poor forage success to the west of Cape Verde compared to the east (Fossette et al 2010). In this scenario, the immature loggerhead sea turtles returning to Cape Verde after their developmental migration certainly had gained previous knowledge about the existence of a food-poor region west of the archipelago and about the existence of a more productive area east of the archipelago, but were likely unaware of the existence of a food-rich continental shelf 500 km east of the archipelago.…”
Section: Discussionmentioning
confidence: 99%
“…The dispersal pattern of young loggerhead sea turtles from Cape Verde has recently been estimated from particle tracking models and drifter trajectories (Monzon- 72 0 0 74 3 0 76 2 0 78 13 0 80 6 0 82 12 0 84 11 0 86 7 1 88 3 1 90 0 1 92 0 3 94 0 1 96 0 0 98 0 2 100 1 1 102 0 0 Table 1 (Bjorndal 1997, Revelles et al 2007, Frick et al 2009, Cardona et al 2012) and a recent study on leatherback sea turtles Dermochelys coriacea revealed low macrozooplankton biomass and poor forage success to the west of Cape Verde compared to the east (Fossette et al 2010). In this scenario, the immature loggerhead sea turtles returning to Cape Verde after their developmental migration certainly had gained previous knowledge about the existence of a food-poor region west of the archipelago and about the existence of a more productive area east of the archipelago, but were likely unaware of the existence of a food-rich continental shelf 500 km east of the archipelago.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, jellyfish continue to be depicted occasionally (see Arai 2005 for examples) as dead ends in the food chains of the sea and/or as a rare source of food for predators (e.g. Condon et al 2011), despite an increasing number of species of fishes (Redeke 1911, Luttenberger 1981, Gorelova & Grudtsev 1986, Kelley 1987, Ates 1988, Arai 1988, Zann 1988: 208, Cerqueira & Haimovici 1990, Hall 1992, Harbison 1993, Massuti et al 1998, Purcell & Arai 2001, Bonaldo et al 2004, Arai 2005, Orsi Relini et al 2010a, Orsi Relini et al 2010b, Chaves et al 2010, Thaler 2012, Cardona et al 2012, Milisenda et al 2014, Battaglia et al 2014, Sweetman et al 2014, Dias & Almeida 2015, birds, reptiles and mammals (Dathe 1989, Ates 1991, Gronert 1992, Shiomi & Ogi 1992, Bell 1996, Zonfrillo 1997, Peglow 1998, Corsi 2000, Arai 2005, Suazo 2008, Cardona et al 2012, Jarman et al 2013, Melville 2013, Jones & Seminoff 2013, other cnidarians and ctenophores …”
mentioning
confidence: 99%
“…However, the scarcity of records about gelatinous zooplankton in cetaceans strongly suggests that they would seldom be eaten as prey; this conclusion is further supported in striped dolphins by stable isotope analysis results (e.g. Cardona et al, 2012). Moreover, the fact that most records about tunicates in the stomach contents of cetaceans involve suction-feeder species may suggest that tunicates are accidentally eaten along with the actual prey (see Walker et al, 2002).…”
Section: Resultsmentioning
confidence: 96%